STRATEGI PEMERINTAH DALAM PELESTARIAN WISATA BENTENG KERATON BUTON DI KOTA BAU-BAU - Anggun, Anggun; Alyas, Alyas; Rasdiana, Rasdiana (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this study was to find out hom the government’s srategi in preserving the torism of th buton place fort in th city of bau-bau. With the number of informant’s in this study amounted to 8 people. This type of research usse a qualitative research and case studies. Data collection tehniques using the methods of observation. Interviews, and documentation. The result of the study indicate that the current government of the city of bau-bau is the management of the buton palace fort tourism wich is trough the tourism office. The result of this study incate that the three sub-strategis of the government, namely govermet strategy, policies and targets of the three sub-districts. That th bau-bau city tourism office is considered to the have been maksimal in protecting and preserving in the buton place fort tourism. The factors that influence the preservation of tourism are the supporting factors, namly community participation and access to infrastructure and the inhibiting factor, namely the absence of the retribution for visitors/tourists. Keyword: government trategy, tourism preservation, buton place fort.